Identifikasi Jenis Bakteri pada Luka Kaki Diabetik berdasarkan Penyebab Luka di Rumah Perawatan Luka dan Poliklinik Luka di Kota Makassar - Nurwahidah Nurwahidah; Saldy Yusuf; Takdir Tahir (Politeknik Kesehatan Kemenkes Mamuju, 2018)
The high incidence of Diabetes Mellitus (DM) causes increased complications associated with DM. One is the Diabetic Foot Ulcer (DFU). Delayed healing in DFU is usually caused by infection. The infection of DFU contains many gram negative (-) and gram positive (+) bacteria, so it is important. To identify the type of bacteria present on the DFU based on the cause. This was an experimental cross sectional study conducted at ETN Center, Griya Afiat, Avaro, Isam Cahaya, RSUP DR. Wahidin Sudirohusodo Makassar and Microbiology Laboratory Hospital Unhas Makassar. There were 29 respondents who met the inclusion criteria. Specimens of wound fluid were taken by swabbing technique. The specimen was inoculated on NA (Nutrient Agar) and MCA (MacConcey Agar) then incubated at 37 ° C for ± 18-24 hours to see bacterial morphology. If a gram negative bacteria (-) is tested biochemically by bacteria is grown on TSI (Tripple Sugar Iron), SIM (Indole Motility Sulfide), citrate urea, kovacks. As for gram positive bacteria (+) in MSA medium (Manitol Salt Agar), catalase (H2O2), incubated for 18-24 hours at 37 ° C, record the results of identification and match the bacterial identification table based on gram properties. Based on morphological test, 29,5% gram negative (-) and Gram positive (+) bacteria were 8.8% in traumatic LKD, with the dominant gram negative (-) species being proteus vulgaris (8.8%) and staphylococcus aureus 8.8%) in the gram bacteria (+). While for non trauma LKD found gram negative bacteria (-) as much as 58.8% and gram positive bacteria (+) 2.9% with the dominant type of bacteria are S.Aureus (2.9%) and P. Mirabilis (17.6%) for gram negative bacteria (-). Identification of bacteria in DFU caused by trauma and non trauma is dominant gram negative bacteria (-). Further research is expected to identify the type of bacteria based on the Wagner and sensitivity of the bacteria.